Plantas hospedadoras de Cerambycidae (Coleoptera) en el Espinal periestépico y en la provincia de Buenos Aires, Argentina - Di Iorio, Osvaldo R (Revista de Biología Tropical, 1996)
The host plants of Cerambycidae (Coleoptera) in the Province of Espinal (Chaquenian Dominion) and the province of Buenos Aires are mainly exotics, cultivated or naturalized, the last ones growing spontaneously and forming little forests. Forty two speeies of Cerambycidae are reported using these plants and other native speeies as hosts. Hylotrupes bajulus, originally introduced and a serious pest of fumiture, is reported for fiest time in spontaneous pine forests in Sierra de la Ventana, south of the province of Buenos Aires.